The results of direct-prospecting geophysical methods used for the detection and localization of zones of hydrogen accumulation and migration in the Earth and the Moon cross-sections - Yakymchuk, M.A.; Korchagin, I.M. (Reports of the National Academy of Sciences of Ukraine, 2021)
The results of experimental studies at the hydrogen production site, hydrogen degassing sites in various regions, as well as on the Moon are presented. Experiments using the direct-prospecting technology of frequency- resonance processing and interpretation of satellite images and photographs are carried out in order to study the features of the deep structure in the areas of hydrogen degassing. The results of instrumental measurements indicate that, in the areas of the basalt volcanoes location with roots at different depths, signals at hydrogen frequencies are almost always recorded. When scanning the cross-section, responses from hydrogen are recorded practically from the upper edges of basalt volcanoes to their roots. Therefore, it can be assumed that basaltic volcanoes are a kind of channels through which hydrogen migrates to the upper horizons of the crosssection and further into the atmosphere. Deep (living) water is synthesized within many basalt volcanoes at a depth of 68 km. Hydrogen-rich water is healing and can be used for wellness purposes. All previously surveyed longevity zones on the Earth are located within basalt volcanoes, in which water synthesized at a depth of 68 km migrates to the surface and is used for the water supply. Hydrogen deposits can be formed by basaltic volcanoes in adjacent sealed reservoirs. The Mali hydrogen production site is located outside the contour of the basalt volcano; hydrogen responses were recorded from marl at the well site. At local sites in the Carpathians, signals from hydrogen are obtained from dolomites and marls. Hydrogen deposits formed near basalt volcanoes in different types of reservoirs can be discovered and localized during areal exploration using the methods of frequency- resonance processing of satellite images and photographs. Direct-prospecting technology can also be used to study reservoirs in crystalline rocks (including basalts). The materials of the article, as well as the previously published results of experimental work in various regions, indicate the advisability of using direct-prospecting methods of frequency–resonance processing of satellite images and photographs to detect zones of hydrogen accumulation in areas, where basalt volcanoes are located, as well as in areas of hydrogen degassing. The use of the mobile low-cost technology will significantly speed up the exploration process for hydrogen, as well as reduce the financial costs for its implementation.